Going online on behalf of someone else: Characteristics of Internet users who act as proxy users. (August 2021) - Reisdorf, Bianca C; Petrovčič, Andraž; Grošelj, Darja
An important contribution of digital inequalities research has been the discussion of nuances in ways that people (dis)engage with information and communication technologies (ICTs). One such practice is proxy Internet use (PIU): indirect Internet access by asking others to do things online for them or on their behalf. Whereas there is a good amount of research on those who are on the receiving end of PIU, users-by-proxy, little is known about "proxy users" who provide PIU. Analyses of nationally representative survey data from Slovenia ( N  = 1047) collected in 2018 show that 51% of Internet users reported to have acted as proxy users in the past 12 months. Multivariate analyses unveil that those Internet users who report a wider array of personal, economic, social Internet uses as well as those with higher levels of operational Internet skills are more likely to act as proxy users.